(untitled) (PerCursos, 2022)
The Covid-19 pandemic is one of the most important phenomenons of our time. Scientists will pore over it for decades to try to understand its effects on the multiple dimensions of life. The following text is an attempt to contribute to this understanding, questioning some of the impacts of the pandemic on the lives of homeless people in Brasília (DF), capital of Brazil. Extensive research has been carried out in Brasília - DF with these populations and, based on a sample, we brought three testimonies that illustrate the processes of intensification of the stigmatization that they suffer. We theoretically approached the theme based on Goofman´s reflections on stigma, but we incorporated other more recent contributions in order to bring to light what has been happening to these groups. The dialogue between theory and field research indicates that, in addition to the interactionist perspective, stigma must be understood within a broader context of power relations and social inequality. Stigma is not a random phenomenon, but has privileged targets, and the groups that suffer from stigma also occupy underprivileged positions in society: ethnic, racial and sexual minorities, carriers of diseases that are mostly endemic among the poorest people including the homeless populations.